ANALISIS PERLAKUAN AKUNTANSI DAN PELAPORAN BELANJA BARANG DAN JASA PADA DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK PROVINSI SULAWESI UTARA - Kojongian, Claudya; Sabijono, Harijanto; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The purpose of this study to Analyses the Accounting Treatment and the Goods and Service spending on Department of Empowerment of Women Employment and Protection of Children of North Sulawesi Province in accordance with applicable regulations. Accounting treatment is the treatment on goods and service include recognition, measurement, presentment, and disclosure. The purpose of this study to determine the accounting treatment on Department of Empowerment of Women Employment and Protection of Children of North Sulawesi Province. The methods used in this research is a qualitative descriptive. The results obtained that The Accounting Treatment of Goods and Service in Department of Empowerment of Women Employment and Protection of Children of North Sulawesi Province is already Accrual based and the reporting has been arranged in accordance with Minister of Home Affairs Regulations No. 64 of 2013 concerning Implementation of accrual Based Government Accounting Standards.Keyword: Analyses, Accounting treatment, Reporting, Goods and service spending